Nourishing Life – Chinese Environmental Wisdom and Practices - Dłużewicz, Alicja (Wydział Filozoficzny UAM, 2020)
Increasingly recognized threats from climate change and the progressive sixth mass extinction require not only searching for new technological solutions, but also changing the perception of the world and the beings living in it. There is an urgent need to include individual practices; practices that are an integral part of integrated policies to protect habitats, the climate, and the homo sapiens itself. Eric S. Nelson, in his latest book Daoism and Environmental Philosophy. Nourishing Life introduces the reader to the environmental approach known to Chinese communities for centuries. In a comprehensive and accurate manner, the author presents the Chinese approach to life and development, the understanding and interpretation of which has changed over the centuries, invariably emphasizing man’s belonging to the world of nature. This review introduces the author’s assumptions presented in the book, combining them with relatively new thoughts and paradigms appearing in the 20th and 21st centuries in Western Europe and the United States.
Keywords: Eric S. Nelson; Daoism; Chinese Philosophy; the natural rhythm of life; nourishing life; environmental philosophy; holistic approach